Frequency of Extracranial Complications of Chronic Suppurative Otitis Media (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Objectives: To see the way of presentation of extracranial complication, relationship between socio-economic conditions and extracranial complication of chronic suppuration otitis media.Methods: This is a cross-sectional study carried out in Department of Otolaryngology Head and Neck Surgery, Sir Salimullah Medical College & Mitford Hospital and Dhaka Medical College Hospital from 1st July 2009 to 30th June 2010. The diagnosis was made by detailed history, clinical examination & investigation. Analyzed data was presented by various tables.Results: In this study male (59%), lower class people (57%), age 11-20 years, rural (66%) and less educated patients were more affected. Having bath in the ponds and rivers suffers more. Clinical presentation of CSOM with complications were aural discharge (100%), hearing impairment (94%), post auricular swelling (15%), pain in the ear (21%), postauricular discharge (27%) and mass in the EAC (12%). Here found aural discharge mostly malodorous and scanty, attic perforation and cholesteatoma. Post auricular abscess most common (47%) extracranial complication and labyrinthitis was the lowest (3%). Atticoantral variety was more common (89%) than that of tubotympanic disease (11%).Conclusion: From the review of the series we found the frequency & types of extracranial complications arising from CSOM and known the current epidemiological data. It can produce awareness among all level of medical practitioners and enhance prompt diagnosis and treatment.J Bangladesh Coll Phys Surg 2016; 34(1): 3-8